On nonlinear Schrödinger problem with amplification process - Čiegis, Raimondas; Kairytė, Genė; Pakalnytė, Violeta (Lietuvos matematikos rinkinys, 2000)
In this paper we consider the nonlinear Schrödinger problem with amplification process. We define a new unknown function and derive a nonlinear equation for this function. Theoretical analysis of a symmetrical finite difference scheme is given and the convergence is proved.